Answer:
Step-by-step explanation:
You already have f(x)= x2
so
3(2x)=6x
I hope this help
![2x - 8 = x + 4](https://tex.z-dn.net/?f=2x%20-%208%20%3D%20x%20%2B%204)
Collecting like terms,
![2x - x = 4 + 8](https://tex.z-dn.net/?f=2x%20-%20x%20%3D%204%20%2B%208)
Since the signs change when its position changes.
![x = 8 + 4 \\ x = 12](https://tex.z-dn.net/?f=x%20%3D%208%20%2B%204%20%5C%5C%20x%20%3D%2012)
Answer:
97.94 is 83% of 118
Step-by-step explanation:
Let the missing number be x
97.94=83% of x
I.e, 97.94=83/100 × x
97.94=83x/100
Cross multipy 97.94/1=83x/100
We have, 97.94 × 100 = 83x × 1
9794=83x
Divide both sides by 83 to make x the subject of the formula.
9794/83=83x/83
118=x
Answer:
1024 or A
Step-by-step explanation:
64 x4 is 256 x4 it's a 1024
Answer:
Step-by-step explanation:
Let the solution to
2x^2 + x -1 =0
x^2+ (1/2)x -(1/2)
are a and b
Hence a + b = -(1/2) ( minus the coefficient of x )
ab = -1/2 (the constant)
A. We want to have an equation where the roots are a +5 and b+5.
Therefore the sum of the roots is (a+5) + (b+5) = a+ b +10 =(-1/2) + 10 =19/2.
The product is (a+5)(b+5) =ab + 5(a+b) + 25 = (-1/2) + 5(-1/2) + 25 = 22.
So the equation is
x^2-(19/2)x + 22 =0
2x^2-19x + 44 =0
B. We want the roots to be 3a and 3b.
Hence (3a) + (3b) = 3(a+b) = 3(-1/2) =-3/2 and
(3a)(3b) = 9(ab) =9(-1/2)=-9/2.
So the equation is
x^2 +(3/2) x -9/2 = 0
2x^2 + 3x -9 =0.